Inferring the seasonal evolution of phytoplankton groups in the Senegalo‐Mauritanian upwelling region from satellite ocean‐color spectral measurements. Issue 9 (30th September 2015) - Farikou, O.; Sawadogo, S.; Niang, A.; Diouf, D.; Brajard, J.; Mejia, C.; Dandonneau, Y.; Gasc, G.; Crepon, M.; Thiria, S.
Abstract We have investigated the phytoplankton dynamics of the Senegalo‐Mauritanian upwelling region, which is a very productive region, by processing a 13 year set of SeaWiFS satellite ocean‐color measurements using a PHYSAT‐like method. We clustered the spectra of the ocean‐color normalized reflectance (reflectance normalized by a reflectance dependent on chlorophyll‐a concentration only) into 10 significant spectral classes using a Self‐Organized Map (SOM) associated with a hierarchical ascendant classification (HAC). By analyzing a 13 year climatology of these classes, we have been able to outline a coherent scenario describing the Senegalo‐Mauritanian upwelling region in terms of spatiotemporal variability of phytoplankton groups: during the onset of the upwelling (December–February), we mainly observed nanoeukaryote‐type phytoplankton in the coastal area; in April–May, the period corresponding to the maximum chlorophyll‐a concentration, the nanoeukaryote types were replaced by diatom types. This scenario is in agreement with microscope phytoplankton cell observations done during several past cruises.